Body weight and body fat are negatively associated with severe dyspareunia in postmenopausal women. Issue 12 (6th September 2022) - Terauchi, Masakazu; Odai, Tamami; Kato, Kiyoko; Miyasaka, Naoyuki
Abstract: Aim: This cross‐sectional study aimed to investigate the factors associated with dyspareunia in pre‐, peri‐, and postmenopausal Japanese women participating in the health and nutrition education program at a menopause clinic. Methods: First‐visit records of 1702 pre‐, peri‐, and postmenopausal Japanese women (aged 40–79 years) were analyzed. The relationship between severe dyspareunia and background characteristics was examined by multivariate logistic regression analysis. Results: The average age of the participants was 53.0 ± 6.3 years. The percentage of women who suffered from severe dyspareunia in the pre‐, peri‐, postmenopausal, and the hormone therapy receiving groups were 7.1%, 10.5%, 14.6%, and 7.8%, respectively. In the postmenopausal group, the percentage of women affected by severe dyspareunia was the highest between 2 and 5 years after menopause (18.8%), presumably owing to the gradual postmenopausal decline in the number of sexually active women. In sexually active postmenopausal women, body weight, body mass index (BMI), and body fat percentage (BF%) differed significantly among those who had severe dyspareunia ( N = 119) and those who did not ( N = 334). BMI and BF% were negatively associated with severe dyspareunia, even after adjustment for age and years since menopause (adjusted odds ratio [95% confidence interval]: BMI, 0.894 [0.825–0.964], p = 0.003; BF%, 0.947 [0.909–0.985], p = 0.006). Conclusions: BMI and BF% were negatively associated with dyspareunia in sexually active postmenopausal women. In addition to aging, the loss of body weight and fat could negatively impact intercourse in sexually active postmenopausal women.